2019
DOI: 10.3389/fphar.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

The South African Medicines Control Council: Comparison of Its Registration Process With Australia, Canada, Singapore, and Switzerland

Abstract: Introduction: Comparisons between regulatory authorities of similar size and regulatory characteristics facilitate value-added benchmarking and provide insight into regulatory performance. Such comparisons highlight areas for improvement as authorities move toward achieving their regulatory goals and stakeholders’ demands. The aims of this study were to compare the registration process and the regulatory review model of the South African Medicines Control Council (MCC) to that of four other similar-sized regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Keyter et al studied the review times for NASs for South Africa in comparison with NRAs in Australia, Canada, Singapore, and Switzerland and found that the South African overall review timelines were substantially longer [13]. The median approval time for NASs achieved from 2008-2017 by the NRAs in Australia, Canada, Europe, Japan, Switzerland, and the United States were approximately four times faster than that achieved by South Africa under the former MCC [11].…”
Section: Regulatory Review Approval Timelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Keyter et al studied the review times for NASs for South Africa in comparison with NRAs in Australia, Canada, Singapore, and Switzerland and found that the South African overall review timelines were substantially longer [13]. The median approval time for NASs achieved from 2008-2017 by the NRAs in Australia, Canada, Europe, Japan, Switzerland, and the United States were approximately four times faster than that achieved by South Africa under the former MCC [11].…”
Section: Regulatory Review Approval Timelinesmentioning
confidence: 99%
“…This stratified approach may also require SAHPRA to consider regulatory trade-offs involving acceptance of surrogate end-points supported by strengthened post-marketing commitments such as the reallocation of regulatory resources from pre-marketing to post-marketing functions [5,17]. As SAHPRA moves forward with the implementation of the newly restructured review process, it is critical to ensure that the quality management system is formalized to support the consistent application of good regulatory, review, and reliance practices within the review process [6,9,13]. Furthermore, in an effort to prove itself as an effective, responsive, transparent, and accountable regulatory authority, SAHPRA should consider the use of the universal methodology for benefit-risk assessment of NASs and progressive quality decision-making practices [6,9,13,18,19].…”
Section: Challenges and Opportunities For Improvementmentioning
confidence: 99%
“…The outcome of participation is the receipt of factual results that can be used to help better convey their mission and needs to policy-makers and other stakeholders as well as to continuously monitor their performance for purposes of improvement of timelines and quality of processes. The results generated by OpERA have been used by agencies to compare their activities against those of similar agencies and to provide the basis for a public discussion of new legislative approaches to the optimization of regulatory procedures [12][13][14].…”
Section: Cirs Operamentioning
confidence: 99%
“…Given the vast workload faced by the EAC MRH initiative, as well as by other regulatory programs across the world, collaborating with peer institutions has become a necessity. Could the initiative deliver a greater public health benefit if it started relying more on existing product assessments carried out by trusted regulatory authorities, as urged by the World Health Organization (WHO) [19] and practiced by other regulatory authorities [20,21] (Box 1)? This could free up the EAC MRH initiative's time and resources to focus on which aspects of the assessments done by other agencies are relevant to EAC countries, as well as on carrying out more good manufacturing practice inspections and pharmacovigilance activities.…”
Section: Best Practices From Other Initiatives Around the Worldmentioning
confidence: 99%
“…In practice, reliance can take many forms, such as establishing a recognition protocol by which the decisions of trusted regulatory authorities (such as WHO's Prequalification Programme, the US FDA, or the EU's medicines assessment and licensing system) are routinely accepted or developing an abridged review process for products already approved by those institutions [20,21].…”
Section: How Regulatory Reliance Workmentioning
confidence: 99%